Effect of Elderly Exercise on Changes in Pain Intensity in Rheumatoid Arthritis Patients In Paranginan Health Center: Effect of Elderly Exercise on Changes in Pain Intensity in Rheumatoid Arthritis Patients In Paranginan Health Center - Rosetty Rita Sipayung; Lasma Rina Efrina Sinurat; Henny Syapitri (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
Rheumatoid Arthritis (RA) is a chronic, systemic disease that typically develops slowly and is characterized by recurrent inflammation of the joints. Elderly gymnastics is a series of movements specifically designed for the elderly, and can be used as an independent therapy to reduce RA pain. This study aims to analyze the Effect of Elderly Gymnastics on Changes in Pain Intensity in Rheumatoid Arthritis Patients at the Paranginan Health Center. The research design used was a Quasi-experimental one group pre test-post test design. The population is all elderly people who have RA. The number of samples in this study were 20 respondents, taken using a random sampling technique. The statistical test used is Wilcoxon. The results of the study showed that the intensity of joint pain before exercise for the elderly experienced severe pain, and afterward experienced mild pain, and there was a significant effect of giving exercise to the elderly on changes in RA pain with a value of p=0.000 (p<0.05). It is expected that the elderly routinely intervene in elderly exercise independently to reduce RA pain.